ICT Utilization in English Language Learning Classroom: A Descriptive Qualitative Study at IMBS Miftahul Ulum Pekajangan Pekalongan - Muhammad Azza Rosyadi; Sarlita D. Matra (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2026)
This study discusses the use of Information and Communication Technology (ICT) in English learning classrooms at IMBS Miftahul Ulum Pekajangan Pekalongan. The purpose of this research is to find out the kinds of ICT used in the classroom, explain why ICT is important in the learning process, and describe how ICT is applied during teaching activities. This research used a descriptive qualitative method with a case study approach. The data were collected through classroom observations, interviews with the English teacher, and documentation such as lesson plans and digital learning media. The results show that several ICT tools, such as laptops, projectors, PowerPoint slides, videos, internet sources, and online platforms, are used to support English learning. The use of ICT helps students become more active, interested, and motivated during the lesson. It also improves classroom interaction and makes it easier for students to understand the material. In the learning process, ICT is mostly used to explain materials, support communication, and help classroom discussions. However, there are still some problems faced during the implementation, such as limited internet connection, lack of facilities, and different levels of teachers’ ability in using technology. In conclusion, ICT has an important role in creating more interactive and student-centered learning, but its implementation still needs better facilities, teacher preparation, and effective integration in teaching.